Wheatgrass Juice Administration and Immune Measures during Adjuvant Chemotherapy in Colon Cancer Patients: Preliminary Results - Adva Avisar; Miri Cohen; Rina Katz; Talia Shentzer Kutiel; Anat Aharon; Gil Bar-Sela (MDPI AG, 2020)
Adjuvant chemotherapy is recommended in high-risk stage II-III colorectal cancer (CC). We examine the effect of daily wheatgrass juice (WGJ) intake in addition to chemotherapy on immune parameters, including IL-6, IL-8, IL-10, IL-12, and white blood cells (WBCs) among CC patients. In a controlled prospective trial, 100 stage II-III CC patients were enrolled. According to patient preference, they were divided into two subgroups, control group and intervention group, 50 patients each, all of whom received the same standard postoperative adjuvant chemotherapy, plus consumption of 60 cc WGJ daily in the intervention group. Blood samples were collected at baseline (T0) and upon treatment termination, 5-6 months later (T1). Cytokine concentrations were assessed using ELISA kits. Anti-inflammatory cytokine IL-10 concentrations were significantly higher in the WGJ group than in the control group at T1. The decline in WBC counts between T0 and T1 was significantly lower in the WGJ group. No significant differences were observed in IL-6, IL-8, and IL-12 concentrations between the study groups. The higher levels of IL-10 and the attenuating of WBC decline during chemotherapy may constitute preliminary evidence of the beneficial effects of WGJ on immune parameters, when given as a supplement to standard care. In light of these preliminary results, WGJ supports immunological parameters during adjuvant chemotherapy. Nevertheless, future studies are needed in order to translate those results to clinical recommendations for cancer survivors.